Hyperbranched polyglycerol-grafted titanium oxide nanoparticles: synthesis, derivatization, characterization, size separation, and toxicology. (28th October 2016) - Qin, Hongmei; Maruyama, Kyouhei; Amano, Tsukuru; Murakami, Takashi; Komatsu, Naoki
Abstract: We have been developing surface functionalization of various nanoparticles including nanodiamond and iron oxide nanoparticles in view of biomedical applications. In this context, TiO2 nanoparticles (TiO2 NP) are functionalized with polyglycerol (PG) to provide water-dispersible TiO2 –PG, which is further derivatized through multi-step organic transformations. The resulting TiO2 –PG and its derivatives are fully characterized by various analyses including solution-phase 1 H and 13 C NMR. TiO2 –PG was size-tuned with centrifugation by changing the acceleration and duration. At last, no cytotoxicity of TiO2 NP, TiO2 –PG, and TiO2 –PG functionalized with RGD peptide was observed under dark conditions.